Aptamers against pathogenic microorganisms. (1st November 2016) - Davydova, Anna; Vorobjeva, Maria; Pyshnyi, Dmitrii; Altman, Sidney; Vlassov, Valentin; Venyaminova, Alya
Abstract: An important current issue of modern molecular medicine and biotechnology is the search for new approaches to early diagnostic assays and adequate therapy of infectious diseases. One of the promising solutions to this problem might be a development of nucleic acid aptamers capable of interacting specifically with bacteria, protozoa, and viruses. Such aptamers can be used for the specific recognition of infectious agents as well as for blocking of their functions. The present review summarizes various modern SELEX techniques used in this field, and of several currently identified aptamers against viral particles and unicellular organisms, and their applications. The prospects of applying nucleic acid aptamers for the development of novel detection systems and antibacterial and antiviral drugs are discussed.